“EVERYONE IS NAKED WHEN TAKING A BATH”. SAITŌ TORAJIRŌ’S FIVE MEN FROM TOKYO AND THE DEMOCRATIZATION IN THE JAPANESE FILM. - Świrkowski, Andrzej (Porównania, 2016)
Among the first films created in Japan after the implementation of new regulations concerning film production under the allied occupation (1945-1952) was Saitō Torajirō’s Five Men from Tokyo produced in the last months of 1945. Although it was shot on location in the barren wasteland of post-war Tokyo Saitō’s film is a comedy satirizing various aspects of life after the national trauma of the lost war. This article is a brief analysis of the ways in which the film adheres to the guidelines devised by the GHQ to promote democratization. The paper also points out how the acclaimed filmmaker attempted to avoid making a simple propaganda movie in the vein of other films produced immediately after the war.